Jane Tolmach Press Release
This press release announces that Jane Tolmach, Oxnard City Councilwoman and former mayor, filed her Declaration of Intention to run for the 36th Assembly District seat vacated by Ken McDonald. It highlights her more than 20 years of public service, including leadership roles in local government, education, transportation planning, and Democratic Party activities. Tolmach identifies key priorities such as establishing a four-year college in Ventura County, ensuring the state pays its fair share of mandated expenses rather than shifting costs to local governments, and strengthening conflict-of-interest protections. The statement presents her as an experienced, responsive candidate prepared to represent Ventura County effectively in Sacramento.